Local and traditional uses, phytochemistry, and pharmacology of Sophora japonica L.: A review. (1st July 2016) - He, Xirui; Bai, Yajun; Zhao, Zefeng; Wang, Xiaoxiao; Fang, Jiacheng; Huang, Linhong; Zeng, Min; Zhang, Qiang; Zhang, Yajun; Zheng, Xiaohui
Abstract: Ethnopharmacological relevance: Sophora japonica (Fabaceae), also known as Huai (Chinese: 槐), is a medium-sized deciduous tree commonly found in China, Japan, Korea, Vietnam, and other countries. The use of this plant has been recorded in classical medicinal treatises of ancient China, and it is currently recorded in both the Chinese Pharmacopoeia and European Pharmacopoeia. The flower buds and fruits of S. japonica, also known as Flos Sophorae Immaturus and Fructus Sophorae in China, are most commonly used in Asia (especially in China) to treat hemorrhoids, hematochezia, hematuria, hematemesis, hemorrhinia, uterine or intestinal hemorrhage, arteriosclerosis, headache, hypertension, dysentery, dizziness, and pyoderma. To discuss feasible trends for further research on S. japonica, this review highlights the botany, ethnopharmacology, phytochemistry, biological activities, and toxicology of S. japonica based on studies published in the last six decades. Materials and methods: Information on the S. japonica was collected from major scientific databases (SciFinder, PubMed, Elsevier, SpringerLink, Web of Science, Google Scholar, Medline Plus, China Knowledge Resource Integrated (CNKI), and " Da Yi Yi Xue Sou Suo (http://www.dayi100.com/login.jsp )" for publications between 1957 and 2015 on S. japonica . Information was also obtained from local classic herbal literature, government reports, conference papers, as well as PhD and MSc dissertations. Results: Approximately 153 chemical compounds, including flavonoids, isoflavonoids, triterpenes, alkaloids, polysaccharides, amino acids, and other compounds, have been isolated from the leaves, branches, flowers, buds, pericarps, and/or fruits of S. japonica . Among these compounds, several flavonoids and isoflavonoids comprise the active constituents of S. japonica, which exhibit a wide range of biological activities in vitro and in vivo such as anti-inflammatory, antibacterial, antiviral, anti-osteoporotic, antioxidant, radical scavenging, antihyperglycemic, antiobesity, antitumor, and hemostatic effects. Furthermore, flavonoids and isoflavonoids can be used as quality control markers for quality identification and evaluation of medicinal materials and their preparations. Information on evaluating the safety of S. japonica is very limited, so further study is required. To enable safer, more effective, and controllable therapeutic preparations, more in-depth information is urgently needed on the quality control, toxicology data, and clinical value of crude extract and active compounds of S. japonica . Conclusions: S. japonica has long been used in traditional Chinese medicine (TCM) due to its wide range of biological activities, and is administered orally. Phytochemical and pharmacological studies of S. japonica have increased in the past few years, and the extract and active components of this plant can be used to develop new drugs based on their traditional application as well as their biological activities. Therefore, this review on the ethnopharmacology, phytochemistry, biological activities, and toxicity of S. japonica offers promising data for further studies as well as the commercial exploitation of this traditional medicine. Graphical abstract: